2022
DOI: 10.1128/jb.00411-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ClpP Dual Isoform Disruption as an Antisporulation Strategy for Clostridioides difficile

Abstract: The Gram-positive bacterium Clostridioides difficile is a primary cause of hospital-acquired diarrhea, threatening both immunocompromised and healthy individuals. An important aspect of defining mechanisms that drive C. difficile persistence and virulence relies on developing a more complete understanding of sporulation. C. difficile sporulation is the single determinant of transmission and complicates treatment and prevention due to the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Another possible approach is to aim for proteins that are involved in the sporulation process. Bishop et al, showed that a genetic ablation in clpP1/clpP2 genes coding caseinolytic protease P (ClpP) impaired the sporulation process [ 24 ]. SpoA is a key regulator of sporulation as its mutation leads to impaired CD growth and reduced spore production [ 25 ].…”
Section: Targeting CD Protein Surface Componentsmentioning
confidence: 99%
“…Another possible approach is to aim for proteins that are involved in the sporulation process. Bishop et al, showed that a genetic ablation in clpP1/clpP2 genes coding caseinolytic protease P (ClpP) impaired the sporulation process [ 24 ]. SpoA is a key regulator of sporulation as its mutation leads to impaired CD growth and reduced spore production [ 25 ].…”
Section: Targeting CD Protein Surface Componentsmentioning
confidence: 99%
“…Another spore-forming pathogen is C. difficile, where it was shown that the 630 strain in sporulation process expressed only the ClpP1 peptidase and ClpX and ClpC chaperone. However, recent studies in the hypervirulent strain R20291 described that clpP1 and clpP2 participate directly in sporulation, considering that an absence of each ClpP isoform leads to altered sporulation phenotypes and the clpP1/clpP2 double mutant exhibiting asporogenic behavior [86] (Table 1).…”
Section: Role Of Clp In Sporulationmentioning
confidence: 99%
“…Moreover, while no regulatory substrates were identified, ClpP was found to be required for sporulation in C. difficile ( Bishop et al, 2022 ). The virulence and resilience of this pathogen to environmental stresses is critically dependent on spore formation ( Shen, 2020 ).…”
Section: The Role Of Caseinolytic Protease In Modulating Virulence An...mentioning
confidence: 99%
“…The virulence and resilience of this pathogen to environmental stresses is critically dependent on spore formation ( Shen, 2020 ). Spores formed from C. difficile clpP1 and clpP2 null mutants were found to be generally heat labile, morphologically abnormal, and they germinated significantly less than their wildtype counterpart ( Bishop et al, 2022 ). Therefore, ClpP appears to be involved in regulating the transition between different life stages of several pathogens to modulate their virulence.…”
Section: The Role Of Caseinolytic Protease In Modulating Virulence An...mentioning
confidence: 99%